GAMBARAN TINGKAT PENGETAHUAN TENTANG NARKOBA PADA REMAJA DI SMK MUHAMMADIYAH 3 PURWOKERTO - Ika Setiyani, Harni; Maryoto, Madyo; Apriliyani, Ita (NHM PRESS, 2024)
The problem of drug has become a significant global issue, with prevalence observed in nearly all countries. In Banyumas, the level of drug, which was ranked third in Central Java in 2022, has increased by 13.2 percent. Adolescents are a demographic that is characterized by an unstable emotional and psychological state, coupled with a high level of curiosity and susceptibility to negative influences. This makes them particularly vulnerable to drug. It is imperative to possess knowledge about drug in order to prevent its occurrence among adolescents. The objective of this study was to ascertain the extent of knowledge regarding drug among adolescents at SMK Muhammadiyah 3 Purwokerto. This study employs a descriptive research design with a cross-sectional approach. The sample size was 80 respondents, selected through simple random sampling. The research instrument employed was a questionnaire. The data were analyzed using univariate analysis. The findings indicated that the majority of students at SMK Muhammadiyah 3 Purwokerto demonstrated a satisfactory level of knowledge regarding drug, with 70 students (87.5%) exhibiting a high frequency of knowledge. Consequently, the level of knowledge about drug among students at SMK Muhammadiyah 3 Purwokerto can be classified as satisfactory.